Pengembangan Perangkat Pembelajaran Berbasis Discovery Learning dan Toulmin Argument Pattern (TAP) untuk Melatih Kemampuan Berpikir Kritis Siswa Pada Materi Pemanasan Global - Arif Rahman Hakim; Wahono Widodo; Titin Sunarti (Postgraduate, University of Mataram, 2023)
This study aims to develop learning tools for the Discovery Learning model based on the Toulmin Argument Pattern (TAP) which are valid, practical and effective for training students' critical thinking skills on global warming. This research is a development research with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and is tested in SMA Negeri 1 Menganti with One Group Pre test â€“ Posttest Design. Data collection through observation, tests and questionnaires. Data analysis techniques using descriptive quantitative analysis, qualitative and parametric statistical tests. The results of the study show that the learning tools developed are in the valid category, the learning tools developed are practical in terms of the implementation of the lesson plans and the learning activities of active students according to the stages of Discovery Learning syntax, the learning tools developed are effective in terms of from Increased critical thinking skills seen from the n-gain in the high category , there is an increase in students' critical thinking skills, there is no difference increasing critical thinking skills from one class to another. Â It was concluded that the discovery learning model based on Toulmin's Argument Pattern (TAP) Global Warming material developed was valid, practical, and effective